The Value of 99mTc-Methylene Diphosphonate Single-Photon Emission Computed Tomography/Computed Tomography in Detecting Atraumatic Costal Cartilage Fracture in Malignant Tumor Patients - Li, Wei; Zhang, Linqi; Li, Wen; Zhang, Rusen (Frontiers in Oncology, 2020)
Objectives To assess the clinical significance and SPECT/CT features of atraumatic costal cartilage fracture (CCF) in patients with malignant tumors. Methods This was a retrospective review of 38 tumor patients with atraumatic CCF referred to SPECT/CT, who were served as the study group (SG). The features of SPECT/CT of atraumatic CCF were assessed. Another 100 tumor patients who underwent chest SPECT/CT and were excluded from CCF were randomly selected as the control group (CG). In all patients (SG+CG), the diagnostic powers for the detection of atraumatic CCF were calculated on CT, SPECT and SPECT/CT. The final diagnosis was based on pathological findings and radiologic follow-up over at least 1 year. Results On SPECT/CT images of atraumatic CCF in SG, fracture lines, irregular calcification, deformation and swelling were respectively noted in 26.3%, 47.4%, 34.2% and 18.4% lesions, low-uptake, moderate-uptake and high-uptake were respectively noted in 13.2%, 52.6% and 34.2% lesions. In all patients (SG +CG), the diagnostic power for detecting atraumatic CCF of CT, SPECT and SPECT/CT were as follows: sensitivity 63.2%, 100.0% and 92.1%, specificity 86.0%, 81.0% and 94.0%, NPV 86.0%, 100.0% and 96.9%, PPV 63.1%, 66.7% and 85.4%, and AUC value 0.746, 0.905 and 0.931. Conclusions Atraumatic CCF has certain characteristic appearances on SPECT/CT. It should be enrolled in the differential diagnoses when costal cartilages of patients with malignant tumors are revealed the abnormal elevated 99mTc-MDP uptake on scintigraphy. SPECT/CT has excellent diagnostic power in detecting atraumatic CCF.